EKUITAS MEREK LOKAL JOGJA DI MATA GENERASI MILLENIALS - Ina Nur Ratriyana (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
Fashion product is one of the highest consumption nowadays. This research focuses on brand equity of local fashion brand in Jogja (i.e., Dagadu, Dowa, and Amazara). The respondents are millennial ranging from 19-24 years old and live in Yogyakarta. This research uses descriptive quantitative method with 5% margin of error. Pre-survey was held before the initial survey; with total 635 respondents who are living in Jogja for minimum one year. The brand equity is measured based on brand awareness, brand quality, brand association, and brand loyalty. From those factors, Amazara has the highest brand equity. Social media is one of the most important factors to boost its success for building brand equity.